The Effect of Administration of Green Bean Juice (Phaseolus Radiates) on Hemoglobin Levels of Public Women with Anemia at The Pratama Cahaya Clinic Lubuk Pakam - Ika Nur Saputri; Lisyah Syaharani Nasution (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Anemia is a condition in which the number of red blood cells or the concentration of hemoglobin in them decreases from normal levels. This study aims to determine hemoglobin levels in postpartum mothers before giving green bean juice and hemoglobin levels in postpartum mothers after giving green bean juice. In conducting this research, the research used a quantitative research design with a one-group pretest-posttest design model, that is, before it was carried out, observations were made on the sample and after treatment, observations were made again. The data collection technique was carried out using a total sampling technique. Based on the research results, the probability of the test results listed in the table shows that the resulting probability is 0.000. This means that the probability < level of significance (? = 0.05) so that Ha is accepted and H0 is rejected. Thus, it can be stated that there is a significant difference between the hemoglobin levels in postpartum mothers with anemia before giving green bean juice (Pretest) and the hemoglobin levels in postpartum mothers with anemia after giving green bean juice (Posttest). The conclusion that can be drawn is that giving green bean juice (Phaseolus Radiates) affects the hemoglobin levels of postpartum mothers with anemia at the Pratama Cahaya Lubuk Pakam Clinic in 2024.